Innovative Activities in Terms of Information Processing - Peter Balco; Martina Drahošová; Michal Greguš; Mojmír Kališ (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
In our contribution we are describing methodological issues of innovation process in terms of information processing. It is the "meta-innovation methodology”. The quality of input information and their processing is a general prerequisite for effective innovation activities. The ability of teams to solve innovative tasks - our different research outputs describe different spontaneous ability to solve logical tasks in teams. The synergistic effect reaches 25-45% of all tested model teams. To effectively deal with existing observations, we consider applying a methodology based on TRIZ modelled in the form of ARIZ.
Keywords: O1; 330; TRIZ; ARIZ; Innovation